2013
DOI: 10.4269/ajtmh.12-0256
|View full text |Cite
|
Sign up to set email alerts
|

Quality of Piped and Stored Water in Households with Children Under Five Years of Age Enrolled in the Mali Site of the Global Enteric Multi-Center Study (GEMS)

Abstract: Water, sanitation, and hygiene information was collected during a matched case-control study of moderate and severe diarrhea (MSD) among 4,096 children < 5 years of age in Bamako, Mali. Primary use of piped water (conditional odds ratio [cOR] = 0.45; 0.34–0.62), continuous water access (cOR = 0.30; 0.20–0.43), fetching water daily (cOR = 0.77; 0.63–0.96), and breastfeeding (cOR = 0.65; 0.49–0.88) significantly reduced the likelihood of MSD. Fetching water in > 30 minutes (cOR = 2.56; 1.55–4.23) was associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 38 publications
3
11
0
Order By: Relevance
“…Each pathway suggests potential interventions to reduce the risks associated with shared sanitation. A previous GEMS paper found shared sanitation access to be an important contributor to MSD, after adjusting for household drinking water practices, suggesting that combination approaches are necessary [ 51 ]. While our data suggest household latrines are the safest option, well-maintained, hygienic shared facilities that consistently ensure safety and privacy and provide access to soap and water for handwashing may motivate facility usage and reduce open defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Each pathway suggests potential interventions to reduce the risks associated with shared sanitation. A previous GEMS paper found shared sanitation access to be an important contributor to MSD, after adjusting for household drinking water practices, suggesting that combination approaches are necessary [ 51 ]. While our data suggest household latrines are the safest option, well-maintained, hygienic shared facilities that consistently ensure safety and privacy and provide access to soap and water for handwashing may motivate facility usage and reduce open defecation.…”
Section: Discussionmentioning
confidence: 99%
“…Considering the Global Enteric Multi-Center Study (GEMS) from 2012, in sub-Saharan Africa, 83% of urban and 49% of rural populations have access to improved water sources, while the numbers are much lower when access to improved sanitation facilities is considered (43% of urban and 23% of rural populations) [46]. Improving these conditions became a strong priority and one of the Millennium Development Goals of the WHO.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have explored the effect of the timing of infection, in relation to children's age, on short term and long term linear growth impairment. An analysis conducted by Richard et al (40) found that diarrhea in the previous 30 days had an effect on weight only, suggesting that a diarrheal episode in a single month does not have a significant association with length in the following 1, 2 or 3 months (40). When they explored the lagged effects of diarrheal episodes on growth over time, they found that the cumulative burden of diarrhea resulted in a measurable effect on growth (40).…”
Section: Timing Of Enteropathogen Infectionmentioning
confidence: 99%
“…An analysis conducted by Richard et al (40) found that diarrhea in the previous 30 days had an effect on weight only, suggesting that a diarrheal episode in a single month does not have a significant association with length in the following 1, 2 or 3 months (40). When they explored the lagged effects of diarrheal episodes on growth over time, they found that the cumulative burden of diarrhea resulted in a measurable effect on growth (40). They also suggest that if there is adequate time between diarrheal episodes that the child may experience catch-up growth (40,41).…”
Section: Timing Of Enteropathogen Infectionmentioning
confidence: 99%
See 1 more Smart Citation